2012
DOI: 10.1016/j.jvs.2012.03.252
|View full text |Cite
|
Sign up to set email alerts
|

A multilayer stent in the aorta may not seal the aneurysm, thereby leading to rupture

Abstract: The multilayer stents are occasionally used for the treatment of complicated aortic aneurysms, including thoracoabdominal aneurysms. No aneurysm-related mortality among patients treated with this technique has been described in the literature to date. We describe a case of rupture of an aortic aneurysm previously treated with a multilayer stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 12 publications
0
47
1
Order By: Relevance
“…Persistent sac perfusion and subsequent aneurysm rupture have been reported by Lazaris and colleagues in 2012 [25]; stent rigidity leading to aortic rupture has been noticed by Ferrero and colleagues in 2013 [26]. Sultan and colleagues [27] recently released a result of 38 patients with TAAAs treated by off-label use of multilayer stents, in which an aneurysm-related mortality rate of 71.1% was documented.…”
Section: Commentmentioning
confidence: 95%
“…Persistent sac perfusion and subsequent aneurysm rupture have been reported by Lazaris and colleagues in 2012 [25]; stent rigidity leading to aortic rupture has been noticed by Ferrero and colleagues in 2013 [26]. Sultan and colleagues [27] recently released a result of 38 patients with TAAAs treated by off-label use of multilayer stents, in which an aneurysm-related mortality rate of 71.1% was documented.…”
Section: Commentmentioning
confidence: 95%
“…Acceptable outcomes are possible with the MFM when used under the instructions for use (IFU, Tables 1 and 2). 13 The aim of this study was to scrutinize thoracoabdominal repairs performed using the MFM outside the IFU and analyze the adverse outcomes. This resulted in dismal clinical outcomes.…”
mentioning
confidence: 99%
“…The probability of aneurysm enlargement or rupture is still existed, because the pressure slightly decreased, the aneurysm wall is still under rather high pressure compared with the same situation of covered stent implantation. If AAA treated by MS with incomplete sac thrombosis, it can lead to further aneurysm enlargement and subsequence rupture [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the MS may not seal the aneurysm, thus leading to rupture. The issue of blood flow resides inside the sac has not completely been solved, keeping the aneurysm enlargement and rupture probable [20]. But clinical experience showed that MS preserves the flow and excludes the aneurysm; the flow velocity outside the MS is then reduced up to 90% [22].…”
Section: Discussionmentioning
confidence: 99%